صلاحيات رئيس الجمهورية في الظروف الإستثنائية في ظل دستور 2020 - مرزوق, أيمن; فدول, زياد (My University, 2023)
إن تركيز جميع الصلاحيات الاستثنائية في يد رئيس الجمهورية في الحالات الاستثنائية وفقًا لتعديل الدستور 2020 يسمح لرئيس الجمهورية بإعلان حالة الطوارئ عن طريق قرار رئاسي وفقًا للشروط المحددة، وتُلغى حالة الطوارئ عندما لا تكون هناك أسباب تبرر إعلانها. يُمكن أيضًا إعلان حالة الحصار عند وجود تهديد للأمن الداخلي للبلاد. أما الحالة الاستثنائية، فتتطلب وجود خطر جسيم يهدد الأمن الداخلي أو الخارجي أو سلامة المواطنين، وتنتهي عند انتهاء الأسباب التي أدى إلى إعلانها، ويكون تأثير سلطات رئيس الجمهورية في الظروف الاستثنائية على مبدأ الفصل بين السلطات والحريات العامة وكذلك فإن تأثير سلطات رئيس الجمهورية على مبدأ الفصل بين السلطات في الظروف الاستثنائية على مبدأ الفصل بين السلطات، ويتم التركيز على صلاحيات رئيس الجمهورية للتدخل في الحريات العامة خلال الظروف الاستثنائية وفق الأسس القانونية والدستورية المعمول بها، فيتم مناقشة المساس المحتمل بالحريات الفردية والجماعية، حيث يكون بإمكان رئيس الجمهورية تقييد حقوق وحريات الفردية والجماعية في ظل تلك الظروف الاستثنائية بموجب القانون والدستور، علاوة على ذلك، يتم استعراض الضمانات القانونية والدستورية المكفولة لحماية تلك الحريات العامة خلال الظروف الاستثنائية، حيث يجب أن يتوافق أي مساس للحريات مع تلك الضمانات، والتي قد تشمل حقوق المواطنين وحماية الحقوق الأساسية المكفولة بالدستور، وضمان النزاهة والمساءلة في اتخاذ القرارات المتعلقة بالحريات العامة. The concentration of all exceptional powers in the hands of the President of the Republic in exceptional cases in accordance with the 2020 amendment of the Constitution allows the President of the Republic to declare a state of emergency by presidential decision in accordance with the specified conditions, and the state of emergency is canceled when there are no reasons to justify its declaration. A state of siege can also be declared when there is a threat to the country's internal security. As for the exceptional case, it requires the existence of a serious danger that threatens internal or external security or the safety of citizens, and it ends when the reasons that led to its declaration have ended. Between powers in exceptional circumstances on the principle of separation of powers, and the focus is on the powers of the President of the Republic to interfere with public freedoms during exceptional circumstances according to the applicable legal and constitutional foundations, so the potential violation of individual and collective freedoms is discussed, whereby the President of the Republic can restrict individual and collective rights and freedoms in In light of those exceptional circumstances under the law and the constitution, in addition, the legal and constitutional guarantees guaranteed to protect those public freedoms are reviewed during exceptional circumstances, as any violation of freedoms must be compatible with those guarantees, which may include the rights of citizens, the protection of basic rights guaranteed by the constitution, and the guarantee of integrity And accountability in making decisions related to public freedoms.
مذكرة ماستر
Keywords: صلاحيات رئيس الجمهورية – مبدأ الفصل بين السلطات – الحالات الإستثنائية.: powers of the President of the Republic - the principle of separation of powers - exceptional cases.